The Effect of Implementing Accounting Information Quality, Performance-Based Budgeting on Local Government Governance (Good Governance) With Management Commitment as A Moderating Variable - Siregar, Mercy Irene Christine; Sudarma, Made; Andayani, Wuryan; Purwanti, Lilik (The International Journal of Accounting and Business Society, 2025)
Purpose — This study examines the effect of accounting information quality and performance-based budgeting on local government governance (good governance) in Papua Province, Indonesia, with management commitment as a moderating variable. Design/methodology/approach — A quantitative approach and survey methodology were used, employing questionnaires distributed to 90 leaders across key Regional Apparatus Organizations (BAPPEDA, BPKAD, Communication and Information Service) in 30 regencies/cities. The study analyzed data from 2019 to 2023 and applied Partial Least Squares (PLS) for hypothesis testing. Findings — The results indicate that both accounting information quality and performance-based budgeting positively affect good governance practices at the regional government level. Furthermore, management commitment strengthens the impact of accounting information quality on governance. However, management commitment is found to weaken the effect of performance-based budgeting on good governance. Practical implications — The findings suggest that provincial governments should emphasize improving accounting information quality and consistently nurture management commitment to foster transparency. Leaders should also recognize the importance of monitoring performance budgeting initiatives to maximize their governance benefits. Originality/value — This paper presents empirical evidence from Papua Province, offering unique insights into the moderating effects of management commitment in public sector governance. The results provide valuable guidance for regional governments aiming to enhance good governance through improved accounting practice and managerial engagement.